Resektionsstrategie bei Nebennierenrindenkarzinomen = Resection strategies for adrenocortical carcinoma - Schimmack, Simon; Strobel, Oliver (Der Chirurg, 2019)
Adrenocortical carcinomas (ACC) are rare and aggressive neoplasms. Due to their high rate of local recurrence and distant metastases (up to 85%) they are associated with a poor survival. The 5‑year survival in ACC patients with lymph node metastasis or local infiltration is 50% and with distant metastasis less than 15%. An R0 resection with locoregional and para-aortic/paracaval lymphadenectomy is the only curative option and reasonable treatment possibility. The treatment of these patients should therefore be planned and carried out in centers. Local recurrences and distant metastases should also be treated with R0 resection when feasible, combined with neoadjuvant/adjuvant chemotherapy and/or radiation. In the case of an asymptomatic non-resectable ACC, debulking operations cannot be recommended. The primary operation can also be done in a minimally invasive procedure if principles of oncological surgery are followed (radical resection, no damage of the tumor capsule, lymphadenectomy), since survival after open and minimally invasive laparoscopic resection was comparable. Palliative resections are only indicated in symptomatic patients.
Online publiziert: 29. August 2018
Gesehen am 22.07.2019